2012
DOI: 10.3791/4219
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Surgical Approach for Intratracheal Administration of Bioactive Agents in a Fetal Mouse Model

Abstract: Prenatal pulmonary delivery of cells, genes or pharmacologic agents could provide the basis for new therapeutic strategies for a variety of genetic and acquired diseases. Apart from congenital or inherited abnormalities with the requirement for long-term expression of the delivered gene, several non-inherited perinatal conditions, where short-term gene expression or pharmacological intervention is sufficient to achieve therapeutic effects, are considered as potential future indications for this kind of approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…Fetal vector delivery by intraamniotic injection (60 ll of vector suspension) was performed as previously described (Carlon et al, 2010(Carlon et al, , 2012. Neonatal vector administration to the airways was performed by sniffing on day 3 postpartum.…”
Section: Vector Delivery To Perinatal or Adult Murine Airwaysmentioning
confidence: 99%
“…Fetal vector delivery by intraamniotic injection (60 ll of vector suspension) was performed as previously described (Carlon et al, 2010(Carlon et al, , 2012. Neonatal vector administration to the airways was performed by sniffing on day 3 postpartum.…”
Section: Vector Delivery To Perinatal or Adult Murine Airwaysmentioning
confidence: 99%
“…Different animal models have been described for intra‐uterine nanoparticles delivery into fetal lungs . Only larger animals, such as sheep, pig and primates, allow the fetoscopic route because of their comparable anatomical size as humans.…”
Section: Discussionmentioning
confidence: 99%
“…20 nm for rAAV), the substance it is dissolved in, usually saline, and its tropism. In the past we have already shown that the distribution of fluospheres was very comparable to that of rAAV2/6.2 delivery and subsequent gene expression in fetal mouse airways …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations